Comparative investigation on aroma profiles of five different mint (Mentha) species using a combined sensory, spectroscopic and chemometric study. (1st March 2022) - Zhang, Jiguang; Li, Man; Zhang, Hongfei; Pang, Xueli
Highlights: Combinatorial extraction techniques are used to capture the volatiles in mint. Aroma of five mint species were compared on molecular and sensorial levels. Potent odorants in five mint species were characterized using sensomics approaches. Differential odorant markers were identified based on multivariate analyses. Abstract: Mint is a widely used aromatic plant, and the aroma varies among different species. The aroma of five mint species, Mentha citrata L. (MC), Mentha piperita L. (MPI), Mentha spicata L. (MSP), Mentha persicaria L. (MPE), and Mentha suaveolens L. (MSU), were comparatively studied on the sensorial and molecular level. Quantitative descriptive analysis revealed that MC presented a pronounced lemon-like note, MSU is dominated by citrus and floral aromas, MPI has a prominent minty flavor, MSP and MPE have a similar scent, both of which are flavored with a spearmint-like note. Forty-one odorants with odor activity values (OAVs) ≥1 were characterized. Principal component analysis and orthogonal partial least squares discrimination analysis based on OAVs indicated that α -citral, menthofuran, isomenthone, menthol, carvone, and linalool were potential odor-active markers for five mint species discrimination. This study herein will provide guidance for mint resources utilization and also aid mint breeding with better flavor.